African wetlands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Burgis. M.J and J.J. Symoens (eds.), 1987. African wetlands and shallow water bodies. ORSTOM